Pengaruh tingkat upah dan pertumbuhan ekonomi terhadap tingkat partisipasi angkatan kerja di Provinsi Riau - Sarsi, Wisna; Putro, Tri Sukirno; Sari, Lapeti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aim to determine how much influence wage rate and economic growth to the Labor Force Participation Rate (LFPR) in Riau Province. With independent variable of wage rate and economic growth is proxy the level of GDP. And dependent variable is Labor Force Participation Rate (LFPR) in Riau Province. Analysis method in this research is descriptive method and data were analyzed using multiple regression model with SPSS version 16. The data obtained from Central Bureau of Statistics and Department of Manpower & Transmigration in Riau Province. The results showed the variable wage rate and economic growth significance influence on Labor Force Participation Rate (LFPR) in Riau Province. How much influence (R2) of independent variable for dependent variable is 75,8%. And 24,2% residu influencing of another factor not descript in this research.Keywords: LFPR, wage rate, GDP.